Factors Hindering the Students in Completing Their Undergraduate Thesis: A Study at an English Education Study Program in Indonesia - Nabila Nur Amalia; Hariswan Putera Jaya (IJLECR (International Journal of Language Education and Cultural Review), 2023)
One of the obligations of undergraduate students at the end of their study is writing a thesis. During the process, students find several problems that can hinder them completing their thesis. This study was aimed at finding and analyzing the factors that hinder the completion of the thesis and how the students try to cope with the factors. This study used a qualitative descriptive approach by using questionnaire and interview as the research instruments. The population in this study was the undergraduate students of the English Education Study Program who were working on or had finished working on their thesis. The results showed that there were ten factors that hindered students' thesis completion. Of the ten factors, the writers categorized them into two parts, namely internal factors and external factors. The internal factors are; health, psychological barriers, academic ability, and approach (attitude and study habits). While external factors are in the form of; family, environment/friends, thesis administration system, thesis advisor guidance process, references, and other activities. If sorted from the factor most experienced by students to the factor least experienced, the results are psychological barriers (92.9%), reference (78.6%), academic ability (74.3%), learning approach (74.3%), thesis advisor guidance (71.4%), thesis administration system (64.3%), health problems (54.3%), family (48.6%), environment/friends (45.7%), and other activities; participating in internal/external campus organization, working, and some unnecessary activities (30%). In facing the factors, students make various kinds of efforts so that they can still complete their thesis project.